Role of endovenous laser therapy in large and very large diameter great saphenous veins. Issue 7 (21st May 2014) - Florescu, Cosmin; Curry, Greg; Buckenham, Timothy
Abstract: Background: The literature suggests that endovenous laser is less efficacious in great saphenous veins (GSVs) with a diameter of greater than 1 cm. This paper describes the efficacy of endovenous laser therapy (EVLT) in ablating GSV with a diameter greater than 1.0 cm. Methods: Retrospective review of consecutive patients undergoing GSV EVLT between 15 November 2012 and 25 July 2013 was performed. GSV with a maximum diameter of ≥1.0 cm were defined as large, those with a maximum diameter of ≥2.0 cm were defined as very large. Results: A total of 38 ablations were reviewed; two patients had bilateral GSV vein ablations. All underwent a 6‐week post‐procedural duplex. There were 20 ablations on veins >1 cm and 4 ablations on veins ≥2.0 cm. Median GSV length was 21.5 cm (16.5 cm for <1 cm, 24.5 cm for 1–2 cm and 24.5 cm for >2 cm). When correcting for length of vein treated, the energy deposited was stable for all patients at 80 J/cm. Tumescent volumes per centimetre were 3.7 mL/cm for veins <1.0 cm and 4.6 mL/cm for veins >1.0 cm. Successful ablation was achieved in 100% of veins independent of size. Conclusion: Ablation rates for large and very large GSVs in our series do not differ from the cohort of patients with GSV < 1.0 cm and from published results for GSVs < 1.0 cm. This supports the use of EVLT for venous insufficiency in the larger diameter GSV typically found in patients on public hospital waiting lists.